The influence of human values on holiday destination choice in Australia and Brazil - Torres, Cláudio Vaz (2007)
Allen and Ng (1999a) proposed a conceptual framework of how consumers' choice of services may be influenced by the human values that they endorse. The aim of this study is to observe which implications cultural differences had on holiday destination choice. The sample consisted of 793 participants (52% Brazilians, 48% Australians; 51% Male; average age = 25y; Education 52% High School), who answered a questionnaire containing: the vertical-horizontal individualism-collectivism Values Scale, the Meaning and Judgment Scale, a Holiday Destination Measure, a Consumption Behavior Measure, and demographics page. The main effect of the country on cultural patterns between Brazil and Australia was observed. The individualist Australians preferred a piecemeal judgment and placed more importance on tangible attributes. Brazilians, who scored higher on collectivism, used affective judgment more. These and other results are discussed in terms of the validity of the model for individuals who endorse cultural values other than individualism.Allen and Ng (1999a) proposed a conceptual framework of how consumers' choice of services may be influenced by the human values that they endorse. The aim of this study is to observe which implications cultural differences had on holiday destination choice. The sample consisted of 793 participants (52% Brazilians, 48% Australians; 51% Male; average age = 25y; Education 52% High School), who answered a questionnaire containing: the vertical-horizontal individualism-collectivism Values Scale, the Meaning and Judgment Scale, a Holiday Destination Measure, a Consumption Behavior Measure, and demographics page. The main effect of the country on cultural patterns between Brazil and Australia was observed. The individualist Australians preferred a piecemeal judgment and placed more importance on tangible attributes. Brazilians, who scored higher on collectivism, used affective judgment more. These and other results are discussed in terms of the validity of the model for individuals who endorse cultural values other than individualism.